Study on the Corrosion Behavior of P110 and P110S Steel in Casing Annulus Fluids - PAN Li-juan, LONG Wu, HUO Jin-hua (Cailiao Baohu, 2021)
For further improving the efficiency of oil and gas field exploration and development, the corrosion behaviors of P110 and P110S steel in casing annulus fluids of injection and production well in oil field at high temperature, medium temperature and low temperature were investigated by corrosion rate, corrosion products and micromorphology analysis. Results showed that the corrosion behavior of P110 and P110S steel was basically the same under the same temperature and annulus liquid condition. The maximum corrosion rate of P110 and p110S in a set of annulus liquid was 0.65 mm/a, and the corrosion rate of the two materials in the two sets of annulus liquid reached the maximum value at 100 ℃. Moreover, the maximum corrosion rate of P110 was 0.04 mm/a, and the maximum corrosion rate of P110S was 0.03 mm/a. Meanwhile, 3D topography analysis showed that P110 and P110S steel had initial signs of local corrosion after corrosion at 140 ℃ in a set of annulus liquid. Finally, the corrosion behavior and the mechanism of P110S steel under CO2 infiltration were studied, showing that CO2 infiltration increased the corrosion rate of steel at high temperature, and the mechanism of local corrosion was electrochemical corrosion of CO2.